EFL Students' Perception on English Tenses Mastery in Improving English Academic Writing - Arsen Nahum Pasaribu (Institut Agama Islam Negeri Palopo, 2022)
This study seeks to uncover the perceptions of EFL students on English tenses mastery and their belief that English tenses mastery ensures better improvement in academic writing. The research was engaged in a mixed method. The quantitative descriptive method was utilized to study the students’ perceptions on English tenses mastery to improve their English academic writing in numerical form and percentage. The qualitative method was focused on the reasons for the students’ low competence and their belief that English tenses mastery can lead to the quality of writing. The data collection used Google form in multiple-choice and short answer forms. A total of 59 EFL students of the English Department of Universitas HKBP Nommensen who took the Academic Writing course participated in this research. The results show that: (1) most of the EFL students were familiar with all the names of the English tenses with a total of 62.7% (37 out of 59 respondents); (2) the most number of students (54.2 respondents) can employ some of the tenses in writing; (3) The main reason for the EFL students is unable to apply English grammar, particularly English tenses in writing practice was due to the lack of students’ English grammatical competence; (4) around 88.1% of the respondents (52 students) believed that mastering English tenses was the key to improve their writing skill. Accordingly, the teachers need to provide an effective method to advance the students’ competence in the use of the English tense in writing. For the researchers, the research findings provide basic evidence to investigate the issues in the future.